The Relationship Of Work-Family Conflict And Spillover To Affective Well Being Of Female Nurses - Mohsen Golparvar; Mahnaz Zeraatie; Raziyeh Salehhi (Tehran University of Medical Sciences, 2015)
Background and Aim: Work-family conflict and spillover are among threatening factors in hospital environment for nurses' well being. The present research aimed to study the relationship of work-family conflict and spillover to affective well being among nurses. Materials and Methods: The research method was correlational and the statistical population consisted of female nurses of two public hospitals, among whom 197 persons were selected using availability sampling method. Data gathering instruments were the previously made questionnaires including work-family conflict questionnaire, work-family spillover questionnaire and affective well being questionnaire. The reliability and validity of the instruments were verified and the data were analyzed using multiple regression analysis. Results: The results of regression analysis revealed that work-family conflict had a significant predictive power for the prediction of negative and positive affect. Also, the results of regression analysis revealed that homework spillover had a significant predictive power for the prediction of negative affect and that free time spillover had a significant predictive power for the prediction of positive affect. Conclusion: The results of the present study showed that work-family conflict and spillover could cause problems to nurses' affective well being. Therefore, it is necessary that nurses be trained to manage work-family conflict and spillover in a suitable way.